Strong Field Laser Physics - Brabec, Thomas (Springer, 2017)
Since the invention of the laser in the 1960s, people have strived to reach higher intensities and shorter pulse durations. High intensities and ultrashort pulse durations are intimately related. Recent developments have shown that high intensity lasers also open the way to realize pulses with the shortest durations to date, giving birth to the field of attosecond science (1 asec = 10-18s). This book is about high-intensity lasers and their applications. The goal is to give an up to date introduction to the technology behind these laser systems and to the broad range of intense laser applications. These applications include AMO (atomic molecular and optical) physics, x-ray science, attosecond science, plasma physics and particle acceleration, condensed matter science and laser micromachining, and finally even high-energy physics.